Problemetising Prospective Primary Teachers’ Understanding of School Textbooks — The Case of EVS - Kaur, Gurjeet (THE PRIMARY TEACHER, 2016)
Problemetising Prospective Primary Teachers’ Understanding of School Textbooks — The Case of EVS Gurjeet Kaur* 2 * Associate Professor, Department of Teacher Training and Non-formal Education (IASE), Faculty of Education, Jamia Millia Islamia, New Delhi Abstract A textbook is a significant curricular input that propels and navigates the curriculum. NCERT Environmental Studies (EVS) textbooks for Classes III to V, written in the light of the National Curriculum Framework−2005, demonstrate an unconventional approach to knowledge and teaching−learning process. However, there has been a growing concern if these textbooks are actually reaching learners or even teachers. Text interpretation, in its intended sense, is often not as straightforward an intellectual activity as may be presumed, and more than text interpretation, it is the teachers’ conceptualisation of EVS that may be needed to be closely examined. This lends support to the view that the teachers need to be facilitated in understanding the content, its transaction and significance. Hence, it is important that the teachers develop an understanding of the textbooks so that they can transact them in the intended sense. This paper discusses the results of an intervention that aims at enhancing future teachers’ understanding of the EVS textbooks.